SHROOM4 Variants Are Associated With X-Linked Epilepsy With Features of Generalized Seizures or Generalized Discharges - Bian, Wen-Jun; Li, Zong-Jun; Wang, Jie; Luo, Sheng; Li, Bing-Mei; Gao, Liang-Di; He, Na; Yi, Yong-Hong (Frontiers in Molecular Neuroscience, 2022)
Objective SHROOM4 gene encodes an actin-binding proteins, which plays an important role in cytoskeletal architecture, synaptogenesis, and maintaining gamma-aminobutyric acid receptors-mediated inhibition. SHROOM4 mutations were reported in patients with the Stocco dos Santos type of X-linked syndromic intellectual developmental disorder (SDSX; OMIM# 300434). In this study, we investigated the association between SHROOM4 and epilepsy. Methods Trios-based whole-exome sequencing was performed in a cohort of 320 cases with idiopathic generalized epilepsy or idiopathic partial epilepsy. Protein modeling was used to assess the damaging effects of variations. Results Six hemizygous missense SHROOM4 variants, including c.13C>A/p.Pro5Thr, c.3236C>T/p.Glu1079Ala, c.3581C>T/p.Ser1194Leu, c.4288C>T/p.Arg1430Cys, c.4303G>A/p.Val1435Met, c.4331C>T/p.Pro1444Leu, were identified in six cases with idiopathic epilepsy without intellectual disability. All patients presented with features of generalized seizures or generalized discharges. These hemizygous variants had no or extremely low allele frequencies in controls and showed statistically higher frequency in the case cohort than controls. All variants were predicted to alter hydrogen bond with surrounding amino acids or decreased protein stability. The SHROOM4 variants reported in patients with SDSX were mostly destructive or duplicative variants; in contrast, the SHROOM4 variants were all missense variants, suggesting a potential genotype-phenotype correlation. The two missense variants associated with SDSX were located in the middle of SHROOM4 protein, whereas variants associated with idiopathic epilepsy were located around the N-terminal PDZ domain and the C-terminal ASD2 domain. Significance SHROOM4 was potentially a candidate pathogenic gene of idiopathic epilepsy without intellectual disability. The genotype-phenotype correlation and sub-regional effect helps understanding the mechanism underlying phenotypic variation.